2007
DOI: 10.1007/s10681-007-9513-4
|View full text |Cite
|
Sign up to set email alerts
|

The genetic relationship between popping expansion volume and two yield components in popcorn using unconditional and conditional QTL analysis

Abstract: Popping expansion volume (PEV) is the most important quality trait in popcorn, while its germplasm is inferior to normal dent/Xint corn in yield. In this study, 259 F 2:3 families, developed from the cross between a dent corn inbred Dan232 and a popcorn inbred N04, were evaluated for their PEV, grain weight per plant (GWP) and 100-grain weight (100 GW) in two environments. The genetic relationship between PEV and GWP, and 100 GW on individual gene loci were evaluated using unconditional and conditional QTL map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 30 publications
(25 reference statements)
1
27
0
Order By: Relevance
“…The present study demonstrated that conditional QTL mapping could identify a greater number of QTL, as well as evaluate the genetic relationships among different significantly correlated traits at the molecular level. Such information could be used in marker-assisted selection for simultaneously improving objective traits (Li et al, 2008). Excluding the influences of CSFIN, CSSN, CSTN, CSFN, CSFON, DFIN, and DFON on LD resulted in the identification of a large number of new QTL that accounted for a high proportion of the phenotypic variation.…”
Section: Qtl Analysis: Corroborations and New Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study demonstrated that conditional QTL mapping could identify a greater number of QTL, as well as evaluate the genetic relationships among different significantly correlated traits at the molecular level. Such information could be used in marker-assisted selection for simultaneously improving objective traits (Li et al, 2008). Excluding the influences of CSFIN, CSSN, CSTN, CSFN, CSFON, DFIN, and DFON on LD resulted in the identification of a large number of new QTL that accounted for a high proportion of the phenotypic variation.…”
Section: Qtl Analysis: Corroborations and New Findingsmentioning
confidence: 99%
“…Recently, a method called multivariable conditional QTL analysis was proposed for analyzing the contributions of component traits to a complex trait and for investigating the genetic relationship between two traits at the QTL level (Wen and Zhu, 2005). This method could be used to determine genetic interrelationships between traits at the level of individual QTL, and to find additional QTL that are undetectable with unconditional mapping (Li et al, 2008). This method has been successfully used to analyze QTL by Guo et al (2005), Zhao et al (2006), Liu et al (2008), andCui et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…A protocol for conditional genetics analysis proposed by Zhu (1995) has been further developed to study closely related traits and to investigate the contribution of each trait to other related traits at the QTL level (Cao 2000;Guo et al 2005;Zhao et al 2006). For significantly correlated traits, a conditional QTL mapping method could be used to dissect the genetic interrelationship between traits at the level of individual QTLs, as well as reveal additional QTLs that are undetectable by unconditional mapping (Li et al 2008).…”
mentioning
confidence: 99%
“…Loci of small effects were also reported in rice (Xu et al 2004;Li et al 2006), wheat (Kirigwi et al 2007;Wang et al 2009) and maize (Lu et al 2003;Li et al 2007Li et al , 2008. Thus, more attention should be paid to the stable, major QTL detected across different growth stages and with positive pleiotropic effects on other traits.…”
Section: Discussionmentioning
confidence: 99%